2013
DOI: 10.1021/jp402311g
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SAMs Derived from Octadecyloxyphenylethanethiols by Sum Frequency Generation

Abstract: Sum frequency generation (SFG) vibrational spectroscopy analyses were performed on self-assembled monolayers (SAMs) formed via the adsorption of 2-(4-(octadecyloxy)phenylethanethiol (R1ArMT), 2-(3,5-bis(octadecyloxy)phenylethanethiol (R2ArMT), and 2-(3,4,5-tris(octadecyloxy)phenyl-ethanethiol (R3ArMT) on gold. SFG spectra showed that the monolayers formed were closely packed and well ordered. It was determined, using orientation analysis, that as additional octadecyloxy chains were attached to the aromatic rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Adapted from [67] A variety of reflection-based vibrational spectroscopies including IR, Raman and sum frequency generation (SFG) have been applied to study adsorbed or reacted surfactant films on surfaces [84,85]. Most work has focused simply on exploring the structure of these films on immersed surfaces, to map features such as molecular tilt or the linearity of the alkyl chain [86], but a few studies have been applied to observe film behaviour within rubbing contacts [87][88]. Beattie and co-workers studied a Langmuir-Blodgett film of zinc arachidate in sliding sapphire/quartz contacts and found that film order was maintained during sliding but some film was transferred from the monolayer to the opposing surface [87].…”
Section: Ofm Research 1990s To Presentmentioning
confidence: 99%
“…Adapted from [67] A variety of reflection-based vibrational spectroscopies including IR, Raman and sum frequency generation (SFG) have been applied to study adsorbed or reacted surfactant films on surfaces [84,85]. Most work has focused simply on exploring the structure of these films on immersed surfaces, to map features such as molecular tilt or the linearity of the alkyl chain [86], but a few studies have been applied to observe film behaviour within rubbing contacts [87][88]. Beattie and co-workers studied a Langmuir-Blodgett film of zinc arachidate in sliding sapphire/quartz contacts and found that film order was maintained during sliding but some film was transferred from the monolayer to the opposing surface [87].…”
Section: Ofm Research 1990s To Presentmentioning
confidence: 99%
“…Although the uncertainty in the fitting is quite large, the d + /r + ratio is always very small, even for times as short as 2 min, indicating a nearly all-trans conformation for the SAM in all cases. In addition, the molecular orientation of the terminal methyl group of the SAMs can be obtained quantitatively from the ratio of the amplitudes for the symmetric and asymmetric CH 3 stretches (r + /r − or B 2 /B 5 in our fittings) in the spectrum with PPP polarization, as described in detail more recently by Jacob et al 41 Figure 5 also shows this amplitude ratio as a function of the adsorption time (black dots). Again, the uncertainty in the fitting is too large for a quantitative interpretation, but the large value for the r + /r − ratio indicates The Journal of Physical Chemistry C that the average methyl orientation is close to the expected value of 27°6 1 and seems to be nearly constant for all adsorption times.…”
mentioning
confidence: 84%
“…In contrast, SFG spectroscopy is a powerful technique to characterize the orientation and conformation of thiol molecules on SAMs, thus providing information at the molecular level, either averaged over large regions (∼milli-meters) or with micrometer resolution, in the case of SFG microscopy. 41 Nevertheless, we showed that its sensitivity to defects in the monolayer is much smaller than in STM, and it is also a more demanding technique in terms of instrumentation and data analysis. The related SHG technique has the advantage of being of simple implementation and capable of probing molecular adsorption in situ and with good temporal resolution (a few seconds), but here we showed that it probes the electronic response of the substrate to molecular adsorption, making it difficult to relate to the SAM molecular structure.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The nonresonant response from gold provides the background signal that interferes constructively with the ODT methyl response to provide the upwards-pointing peaks, and destructively with the response from the octadecanol methyl group resulting in downwards-pointing peaks. The versatility of this method is evidenced by the range of molecules and interfaces it has since been applied to, providing phase information from polymer-metal interfaces, 18 lipid bilayers and cell structures, [19][20][21] monolayers, [22][23][24][25][26] and immobilized proteins. 17,27 The above method for phase detection allows the relative phase of the resonant modes to be determined.…”
Section: Introductionmentioning
confidence: 99%